2020
DOI: 10.3390/jcm9103209
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Bioavailability and Plasma Antiradical Capacity in Healthy Subjects after Acute Intake of Pigmented Rice: A Crossover Randomized Controlled Clinical Trial

Abstract: Health-promoting effects of plant foods have been emphasized in the last few decades and ascribed to the bioactive phytochemicals present therein—in particular, phenylpropanoids. The latter have been investigated for a number of preclinical biological activities, including their antioxidant power. Due to the paucity of human studies, in this randomized intervention trial, we investigated whether the acute intake of pigmented rice could increase the plasma bioactive levels and antiradical power in twenty health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…Chu et al [ 37 ] developed an extraction procedure for wild rice to facilitate the determination of proanthocyanin content. A randomized trial on 19 human volunteers by Vitalini et al [ 38 ] showed that consumption of two black rice bran cultivars significantly increases plasma levels of polyphenols and flavonoids, and antioxidative capacity. A prospective cohort study showed that multi-grain rice diets decreased the risk of breast cancer in Korean women ( n = 93,306) by 33% as compared to a 35% higher risk for those consuming white rice diets [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chu et al [ 37 ] developed an extraction procedure for wild rice to facilitate the determination of proanthocyanin content. A randomized trial on 19 human volunteers by Vitalini et al [ 38 ] showed that consumption of two black rice bran cultivars significantly increases plasma levels of polyphenols and flavonoids, and antioxidative capacity. A prospective cohort study showed that multi-grain rice diets decreased the risk of breast cancer in Korean women ( n = 93,306) by 33% as compared to a 35% higher risk for those consuming white rice diets [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitalini et al . (2020) stated an increase in serum polyphenols and flavonoids content in human administrated with diet rich in flavonoid‐packed pigment black rice. The indigenous rice like Njavara, medicinal rice from Kerala known for their therapeutic potential (anti‐inflammatory effect) due to presence of unique flavonolignans (4′‐O‐(erythro‐β guaiacylglyceryl) ether and tricin 4‐O‐(threo‐β‐guaiacylglyceryl) ether) (Mohanlal et al ., 2011).…”
Section: Health Promoting Propertiesmentioning
confidence: 99%
“…Through their regulation of cell signaling pathways, flavonoids may help prevent cancer by increasing phase II detoxifying enzyme activity, decreasing proliferation, and triggering apoptosis. When human participants were fed pigmented black rice high in flavonoids, serum polyphenols and flavonoids levels were shown to be enhanced compared to baseline values ( Vitalini et al, 2020 ). Bioactive compounds found in cereals possess antioxidative properties, which in turn counter various diseases such as heart disorders, cancer, aging, and inflammatory diseases ( Espitia-Hernández et al, 2020 ).…”
Section: Phenolic Compound-rich Bioactive Ingredients In Cereals For Sustained Human Healthmentioning
confidence: 99%